2008
DOI: 10.3171/spi/2008/8/2/129
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of peripheral nerve sheath tumors of the second cervical nerve root in 60 surgically treated patients

Abstract: Object This study is a retrospective analysis of 60 surgically treated patients with 64 peripheral nerve sheath tumors (PNSTs) at the second cervical (C-2) nerve root. The anatomical subtleties of these tumors and their implications for surgical strategy when compared with other spinal PNSTs and other tumors in the foramen magnum region are reviewed. Methods Sixty patients with C-2 PNSTs treated surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Therefore, working within the dural confines and respecting the dural cover of the tumor can lead to radical and safe tumor resection. We think that such surgical technique may be insufficient and needs to be modified in the case of extensive extension to the paraspinal region, such as Type C. [1][2][3]8,11,15) In our series, we encountered a single case of spinal NST originating from C1 not associated with neurofibromatosis. Non-neurofibromatosis NSTs originating from C1 are extremely rare.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Therefore, working within the dural confines and respecting the dural cover of the tumor can lead to radical and safe tumor resection. We think that such surgical technique may be insufficient and needs to be modified in the case of extensive extension to the paraspinal region, such as Type C. [1][2][3]8,11,15) In our series, we encountered a single case of spinal NST originating from C1 not associated with neurofibromatosis. Non-neurofibromatosis NSTs originating from C1 are extremely rare.…”
Section: Discussionmentioning
confidence: 86%
“…Various surgical approaches have been applied to resect dumbbell-shaped or extradural tumors of the cervical spine, but excessive bone resection and soft tissue T. Takami et al manipulation appear to be unnecessary in the majority of spinal NSTs originating from the C1 or C2 level. [2][3][4]8,9,11,15) In an exceptional case, another surgical strategy such as an anterolateral approach with management of vertebral artery may be adequate to resect tumor involving the vertebral artery or extending beyond the vertebral artery, which is one of the limiting factors of the radical resection. 2,15) Excessive bone resection for wide exposure of the tumor may necessitate a subsequent fusion procedure such as posterior occipitocervical or C1-2 fixation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many clinicians believe that the reconstruction of cervical spine instability is an important aspect of high cervical spinal tumor treatment (12,18,24). According to Goel, because C2 schwannomas are in most cases located at the ganglion and are subdural, and because they are located between the atlas and atlantoaxial joint, as well as inside the atlantoaxial joint, resection of the atlantoaxial posterior arch and vertebral body to fully expose and remove the tumor is not required (9). In this group of patients, we found that the C1-2 spinal bodies were wider, and the average sagittal diameter was 20-23 mm (14).…”
Section: Long-term Follow-upmentioning
confidence: 99%